A contribution to the study of the habits and bionomics of the Stenoscelis hylastoides (Woll.), a wood-boring beetle pest of the Western Cape Province - Zinn, Jack (Department of Biological Sciences, 2016)
Includes bibliographical references (pages 68-69).